The Legal - Jurisprudential Examination of the Role of Will in the Agreements between Parents with Custody Issue - Majid Reza Kamali Banyani; Dawood Nasiran; Sayyed Muhammad Hadi Mahdavi (آموزه‌‌های فقه مدني)
Before the enactment of The Family Protection Act of Iran (1391), the agreements for the acceptance of the right of custody or to pay special privilege to other parent takes place they had not explicitly been attached to the legal ruling case. But after the enactment of the mentioned law in Article 41, it has been implicitly legitimized. For the most important factor to perform agreements is will and agreement of both parties. The principle is the party autonomy and because custody is the parents' right and responsibility. Each party can give the exercise of the right and performance of the responsibility based on these agreements to other party if it does not stipulate that the obligor or accountable person should directly implement the liability. This paper has examined the role of parents’ will on concluding agreements between parents with each other or with the third person. With observing this research, it is understood that in the law of Iran custody based on its dual nature cannot be waived or assigned but parties can representatively transfer the performance of right to an agent. Therefore, it is possible to conclude these agreements in the time of marriage or divorce, consequently, the possibility of assignment to the third party (private enterprises-organizations-, employing nurses, giving the custody of children to the social workers…) it is in the formation of nominate contracts-defined contracts- such as leas, sulh, wakalah, ju'alah, … or in the formation of innominate contracts (Article 10 of the civil code). Because the principle of autonomy in the agreements of custody is more limited than the other contracts, Child’s benefits as specifier (Arabic: مخصص mukasis) is constantly considered by the courts.